2019
DOI: 10.3126/bjhs.v4i2.25437
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Occurrence of Ocular Injuries and their Forensic Aspects

Abstract: Introduction: All penetrating or non-penetrating intentional ocular trauma causing loss of an organ or part of an organ and which have as a consequence the facial disfigurement or post trauma sequelae formation have forensic implications. Objectives: To study the pattern of ocular injuries its forensic implications and meticulous documentation in ocular medicolegal cases. Methodology: This hospital based cross sectional study was carried out by Forensic medicine personnel in Department of Ophthalmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Amjad et al had also reported 65% male patients with trauma in their study 8 . In the study by Timsinha et al, 69.32% were males 13 . Globally male gender is reported to be more vulnerable for ocular injuries.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Amjad et al had also reported 65% male patients with trauma in their study 8 . In the study by Timsinha et al, 69.32% were males 13 . Globally male gender is reported to be more vulnerable for ocular injuries.…”
Section: Discussionmentioning
confidence: 87%
“…Amjad at al had reported that 32.5% of their patients were between 21 to 30 years of age8. Study published in Nepal had reported that 26.30% patients were between 21-30 years of age 13 . In our study, 57.6% patients were between 18-25 years of age.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Timsinha et al in their study reported that cornea was affected most commonly in 47.81% trauma cases while 31.87% cases had abnormal findings in conjunctiva 21. Open globe injuries were related to worse BCVA at presentation in comparison with closed globe injuries (p=0.001).…”
mentioning
confidence: 89%